Manipulating immune checkpoint signalling pathways with antibodies - Paluch, C (2019)
Immune checkpoint receptors are critical regulators of immune tolerance. Antibodies blocking these pathways can enhance immune responses and in recent years have revolutionised the treatment of cancer. The converse approach of developing agonistic antibodies against checkpoint receptors to dampen immune responses has not been widely explored, and whether this could present an effective new approach for the treatment of autoimmune disease remains an open question. We have characterised panels of antibodies against three human immune checkpoint receptors: BTLA, TIGIT and CD200R. For each of these targets we have also characterised a transgenic mouse strain expressing the human form of the protein in a functional pathway, allowing for the assessment of translatable anti-human antibodies in the physiological context of an intact immune system. Using these transgenic mice we demonstrated that a BTLA agonist antibody can inhibit T cell responses in vitro and in vivo and that this can have a meaningful therapeutic impact in murine models of autoimmune disease. Utilising a collection of engineered antibodies as tool reagents we showed that antibody agonism of checkpoint receptors is dependent on Fc receptor engagement and sensitive to the dimensions of the antibody. This supports a mechanism of antibody agonism compatible with the kinetic-segregation model of receptor triggering, in which an immobilised antibody induces triggering by holding the receptor in the contact between two cells, leading to physical exclusion of the bulky receptor-type phosphatases that normally restrain signalling. Our results set the scene for the future clinical development of checkpoint agonists as a novel class of immunosuppressive therapeutic and provide insights into how such agents can be designed and optimised for maximal efficacy.